2022
DOI: 10.1111/jam.15218
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography can detect previsual bacterial growth in a laboratory setting via metabolic heat detection

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Hunt and colleagues demonstrated that infrared thermography could identify the existence of E. coli and Staphylococcus aureus by detecting an increase in temperature before they become visible in a solid culture. 98 When cells were exposed to UV light and later treated with diazophenol, a decrease in temperature was observed followed by an increase in heat.…”
Section: Culture-based Methodsmentioning
confidence: 99%
“…Hunt and colleagues demonstrated that infrared thermography could identify the existence of E. coli and Staphylococcus aureus by detecting an increase in temperature before they become visible in a solid culture. 98 When cells were exposed to UV light and later treated with diazophenol, a decrease in temperature was observed followed by an increase in heat.…”
Section: Culture-based Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Previous studies have revealed that three key factors including the bacterial load, temperature, and immune response affect each other during bacterial infection. 9,10 When bacterial infection occurs, the temperature of the infected organism increases, triggering a heat shock response in the body. 11,12 Bacteria secrete toxins that trigger inflammatory responses and activate immune cells.…”
Section: Introductionmentioning
confidence: 99%